"Clip first" policy in management of intracranial MCA aneurysms: Single-centre experience with a systematic review of literature - Steklacova, Anna; Bradac, Ondrej; Charvat, Frantisek; De Lacy, Patricia; Benes, Vladimir (Acta neurochirurgica, 2016)
BACKGROUND: The results of microsurgical treatment for middle cerebral artery (MCA) aneurysms (ANs) have been highly satisfying for decades, notoriously posing a challenge for interventional neuroradiologists. Following the International Subarachnoid Aneurysm Trial (ISAT) study results, most centres across Europe and the USA switched to a "coil first" policy. The purpose of this study is to evaluate and critically review the substantiation of this change. METHODS: The authors conducted a single-institution retrospective study of MCA AN treatment between January 2000 and December 2013 maintaining a "clip first" policy. The results are supplied with a literature review. RESULTS: A total of 315 MCA ANs were treated in 288 consecutive patients (209 females, 79 males). Microsurgical treatment was performed for 238 AN patients (116 ruptured, 122 unruptured) and 77 AN patients (46 ruptured, 31 unruptured) who underwent a coiling procedure. Treatment-related morbidity and mortality (MM) for unruptured ANs was 2.8 % in the microsurgical group and 10.3 % in the endovascular group. The percentage of patients with no/minor permanent neurological deficits after SAH in a good initial clinical state (HH 1-2) was 93 % in the microsurgical and 76 % in the endovascular group. A literature review identified 21 studies concerning MCA AN treatment with a specified decision-making algorithm. Microsurgery seemed superior to endovascular management regarding both clinical and radiological outcomes, although several aspects of the analysed reports might appear questionable. CONCLUSION: Although this study has its inherent limitations, the effect brought about by microsurgical clipping of MCA ANs remains superior to that of endovascular embolisation and it should be sustained as the first treatment choice. The decision about the treatment strategy should be made by a multi-disciplinary team consisting of specialists from both teams, bearing in mind the higher occlusion rate and longevity of the surgical treatment.
Keywords: Male; retrospektivní studie; mikrochirurgie; Embolization, Therapeutic; Adult; Aged; dospělí; Practice Guidelines as Topic; mužské pohlaví; senioři; Intracranial Aneurysm; lidé; Surgical Instruments; ženské pohlaví; Microsurgery; Humans; chirurgické nástroje; terapeutická embolizace; Retrospective Studies; Female; intrakraniální aneurysma; lidé středního věku; směrnice pro lékařskou praxi jako téma; Middle Aged